2018
DOI: 10.1111/jomf.12527
|View full text |Cite
|
Sign up to set email alerts
|

Gender Gap in Repartnering: The Role of Parental Status and Custodial Arrangements

Abstract: Objective: This study assesses whether parenthood influences repartnering for women and men and explores how repartnering is associated with parental status of the prospective partners. Background: Previous research has not demonstrated whether gender differences in repartnering are conditional on the presence of children. This study aims to better disentangle the specific gender differentials in repartnering probabilities conditional on parenthood and child custody status. Method: The analytical sample consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 61 publications
(129 reference statements)
2
23
0
Order By: Relevance
“…Looking beyond the United States, where studies tend to investigate repartnering broadly to include marriage or cohabitation, a large body of work indicates that mothers in multiple countries have lower rates of repartnering than fathers (e.g., Di Nallo, ; Gałęzewska, Perelli‐Harris, & Berrington, ; Gray, ; Ivanova, Kalmijn, & Uunk, ). However, some evidence indicates that parenthood is only associated with reduced repartnering when parents live with their children (e.g., Beaujouan, ; Vanassche, Corijn, Matthijs, & Swicegood, ).…”
Section: Demography and Predictors Of Remarriage And Repartnershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking beyond the United States, where studies tend to investigate repartnering broadly to include marriage or cohabitation, a large body of work indicates that mothers in multiple countries have lower rates of repartnering than fathers (e.g., Di Nallo, ; Gałęzewska, Perelli‐Harris, & Berrington, ; Gray, ; Ivanova, Kalmijn, & Uunk, ). However, some evidence indicates that parenthood is only associated with reduced repartnering when parents live with their children (e.g., Beaujouan, ; Vanassche, Corijn, Matthijs, & Swicegood, ).…”
Section: Demography and Predictors Of Remarriage And Repartnershipmentioning
confidence: 99%
“…However, some evidence indicates that parenthood is only associated with reduced repartnering when parents live with their children (e.g., Beaujouan, ; Vanassche, Corijn, Matthijs, & Swicegood, ). Studies from multiple countries indicate that childless men and women have similar likelihoods of repartnering (e.g., Beaujouan, ; Di Nallo, ; Gray, ; Ivanova et al, ). Leveraging a change in custody law in Belgium, Schnor, Pasteels, and Van Bavel () demonstrated that Flemish mothers with sole custody were less likely to repartner than those with shared custody, even though mothers with sole custody also tended to have other characteristics (e.g., high family orientation) associated with higher rates of remarriage.…”
Section: Demography and Predictors Of Remarriage And Repartnershipmentioning
confidence: 99%
“…Studies on divorce have generally found re‐partnering to offset part of the negative effects of union dissolution on women's wealth, but even after remarriage, their wealth remains lower compared to the continuously married (Painter et al, 2015; Wilmoth & Koso, 2002). At the same time, given that men in general re‐partner more often and faster than women (Di Nallo, 2019), re‐partnering might actually increase the average gap in wealth between men and women following union dissolution.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, men are likely to hold more absolute wealth immediately after a divorce which can be invested, as pre-marital wealth differences are not considered in the division of property and thus maintained. Although re-marriage has been shown to be a viable strategy to increase available income after divorce (Jansen et al, 2009) and to partially recover wealth (Wilmoth & Koso, 2002), men are more likely to re-partner than women, particularly if women reside with children (Di Nallo, 2018). Thus, I anticipate wealth accumulation to be lower for women than men in the postdivorce years, leading to men's quicker recovery of wealth losses than women (Gendered Recovery Hypothesis).…”
Section: Gender Differences Over the Marital Dissolution Processmentioning
confidence: 99%
“…The presence of children has also been shown to limit residential parents' likelihood to re-partner and speed of re-partnering. Single parents thus benefit less or only at a later stage from the potential economic benefits of a new relationship (de Graaf & Kalmijn, 2003;Di Nallo, 2018;Pasteels & Mortelmans, 2017;Wu & Schimmele, 2005).…”
Section: Gender Differences In Initial-levels Differences and Growth mentioning
confidence: 99%